Clinical Response to Osimertinib Compared to Other Tyrosine Kinase Inhibitors and Chemotherapy in Non-Small Cell Lung Cancer - Paola, Sánchez-Ríos Carla; Fabián, Martínez-Herrera José; Jordi, Guzmán-Casta; Rodrigo, Riera-Sala; Jorge, Guzmán-Huesca; Sonia, Carrasco-CaraChards; Mart (Archives of Clinical and Medical Case Reports, 2020)
Osimertinib targets the same activating mutations in the EGFR (exon 19 and L858R of exon 21) as other target therapies but it also has action over the T790M mutation (the most frequently resistance mutation found in these tumors) and has better efficacy than 1st and 2nd generation TKI at the Central Nervous System (CNS) level. In Mexico has a higher incidence alterations of the EGFR gene are higher, being the most frequent molecular alteration in up to forty percent of patients with advanced NSCLC and the mutation resistance in T790M is 50% in this group. Here we present 3 cases of patients who received Osimertinib as a 2nd line therapy for metastatic NSCLC obtaining a complete response in one of them. <gdiv></gdiv>